Bond strength to root dentin and fluid filtration test of AH Plus/gutta-percha, EndoREZ and RealSeal systems (Journal of Applied Oral Science, 2013)
OBJECTIVES: To investigate the bond strength and seal ability produced by AH Plus/gutta-percha, EndoREZ and RealSeal systems to root canal dentin. MATERIAL AND METHODS: Sixty extracted single-root human teeth, instrumented manually to size 40, were divided into three groups (n=20) according to the sealer used; G1: AH Plus, G2: EndoREZ, and G3: RealSeal sealers. After filling using the lateral condensation technique, each sealer group was randomly divided into two subgroups according to the tests applied (n=10 for µPush-out test and n=10 for fluid filtration test). A fluid filtration method was used for quantitative evaluation of apical leakage. Four 1-mm-thick slices (cervical and medium level) were obtained from each root sample and a µPush-out test was performed. Failure modes were examined under microscopy at 40x, and a one-way ANOVA was applied to analyze the permeability. Non-parametrical statistics for related (Friedman's and Wilcoxon's rank tests) or unrelated samples (Kruskal-Wallis' and Mann-Whitney's tests) allowed for comparisons of µPush-out strength values among materials at the different levels. Statistical significance was accepted for p values